2018
DOI: 10.3329/bjms.v17i1.35287
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective clinico-pathological study of hysterectomy cases in a tertiary care hospital in India – a review of 950 cases.

Abstract: Abstract:Introduction: Hysterectomy is the most commonly performed gynaecological surgery in India as well as in abroad. It is frequently done in myometrial and endometrial pathologies and rarely for other causes. Hysterectomy is definitive management for diseases like fibroid, adenomyosis, dysfunctional bleeding, prolapsed uterus and malignant lesions of uterus and adenexa. We aimed our study to observe incidence of different pathologies of uterus and other reproductive organs in hysterectomy specimens and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 3 publications
(4 reference statements)
6
7
0
Order By: Relevance
“…Overall incidence of endometrial carcinoma in hysterectomy specimens was found to be 1.21% which is similar comparable to Subrata et al Overall incidence of ovarian tumors in hysterectomy specimens is 10.4% and benign tumors constituted 66.3% in the present study compared to Subrata et al which reported 8.42% tumors with 63.5% benign tumors [13]. Correlation of clinical diagnosis with the histopathologic diagnosis in the present study showed 94.5% correlation, that was comparable to study by Lee et al (80%), Gupta et al and Gangadharan et al (95%) [10,15,28].…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Overall incidence of endometrial carcinoma in hysterectomy specimens was found to be 1.21% which is similar comparable to Subrata et al Overall incidence of ovarian tumors in hysterectomy specimens is 10.4% and benign tumors constituted 66.3% in the present study compared to Subrata et al which reported 8.42% tumors with 63.5% benign tumors [13]. Correlation of clinical diagnosis with the histopathologic diagnosis in the present study showed 94.5% correlation, that was comparable to study by Lee et al (80%), Gupta et al and Gangadharan et al (95%) [10,15,28].…”
Section: Discussionsupporting
confidence: 88%
“…High percentage of endometrial hyperplasia in the age group may be due to obesity, diabetes and sedentary lifestyle [27]. Incidence of malignancy in the hysterectomy specimens in this study was 7.75% which was comparable to Subrata et al (7.68%) and Gupta et al (4%) [10,13].…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…9 Hysterectomy may be performed via abdominal or vaginal routes, depending on pathology, indication for undergoing procedure and surgeon's expertise. 8,10 It is considered important that women should be counseled by her health care provider in detail regarding available treatment modalities and alternate treatment options should be informed to involve her in decision making before undergoing such major surgical procedure. 11 Hysterectomy is a major surgical procedure in terms of both morbidity and mortality.…”
Section: Introductionmentioning
confidence: 99%